A mouse model that is immunologically tolerant to reporter and modifier proteins - Bresser, Kaspar; Dijkgraaf, Feline E.; Pritchard, Colin E. J.; Huijbers, Ivo J.; Song, Ji-Ying; Rohr, Jan C.; Scheeren, Ferenc A.; Schumacher, Ton N. (Communications biology, 2020)
Reporter proteins have become an indispensable tool in biomedical research. However, exogenous introduction of these reporters into mice poses a risk of rejection by the immune system. Here, we describe the generation, validation and application of a multiple reporter protein tolerant ‘Tol' mouse model that constitutively expresses an assembly of shuffled reporter proteins from a single open reading frame. We demonstrate that expression of the Tol transgene results in the deletion of CD8 + T cells specific for a model epitope, and substantially improves engraftment of reporter-gene transduced T cells. The Tol strain provides a valuable mouse model for cell transfer and viral-mediated gene transfer studies, and serves as a methodological example for the generation of poly-tolerant mouse strains. Bresser and Dijkgraaf et al. develop the ‘Tol’ strain, a genetically modified mouse model that expresses a range of shuffled reporter and modifier proteins from a single open reading frame. This strain is immunologically tolerant to these reporter and modifier proteins, providing a valuable model system for cell transfer studies and virus-mediated gene transfer studies.